Deltoid Ligament Release for Varus Deformity Correction in Total Ankle Arthroplasty - Joseph R. Duff MD; Shumaila Sarfani MD; Tyler Ward MD; Jesse F. Doty MD; Garnett Murphy (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis; Ankle Introduction/Purpose: Total ankle arthroplasty (TAA) with severe varus ankle deformity is balanced in the coronal plane by releasing medial soft tissue constraints. There are no previous reports examining the impacts of TAA with concomitant release of the deltoid. Progressive talar tilt and progressive collapsing foot deformity were evaluated. Methods: A retrospective review included patients undergoing TAA with confirmed preoperative varus deformity. Patients underwent complete soft tissue release of the deltoid ligament complex. Pre- and post-operative weightbearing radiographs quantified Meary’s angle, lateral talo-1st metatarsal angle, calcaneal pitch, talar coronal alignment, and the lateral distal tibial angle. The primary endpoints were degrees of coronal plane correction, longitudinal arch position, and complication rates. Results: Thirty-two patients were included with median 12.5 month follow-up. Coronal plane alignment and VAS pain scores improved significantly in all patients, and statistical analysis revealed that complete deltoid ligament release had no bearing on calcaneal pitch and Meary’s angle at final follow-up. Posterior tibial tenotomy was performed on 3 (9.3%) patients. Median coronal plane alignment correction averaged 17.5° improvement (X2(2)= 50.358, P<.001) from 19.5° varus (11.2-24.5°) to 2.0° varus (0.5- 3.5°)(P <.001). Two degrees of coronal plane varus alignment without tilt progression (0.6-3.4°)(P <.001) was maintained through follow-up. Final calcaneal pitch of 18.2° (14.4-23.2°) mirrored initial median measurement of 18.3° (15.7-21.1°). No significant differences were found between Meary’s angle measurements at any time points (P=.568). Eight of 32 patients had complications with five requiring further ankle surgery. Conclusion: Complete release of the deltoid ligament may improve coronal malalignment when performing TAA. Release did not lead to radiographic or clinical medial instability, valgus talar tilt, or medial arch collapse.